Pengembangan Aset Tiga Dimensi Berbasis Photo-Realism untuk VR-Patient Room (Studi Kasus Rawat Inap RSI Jemursari) - Rizqi Putri Nourma Budiarti; Fajar Annas Susanto (Unusa Press, 2019)
The development of information in a hospital is very fast-growing, where the hospital wants to provide services in the form of information about the hospital using Virtual Reality technology. Likewise with Jemursari Islamic Hospital, which is developing the VR-Patient Room application. For the development of VR-Patient Rooms, several assets are needed in the form of devices or equipment located in the hospital. In this study, assets were developed using the photo-realism method. Assets are built by following the criteria of photo-realism, following the scale of size and using 3D applications. Assets built include patient beds, furniture (tables, guest sofas, wall clocks), trash bins, and patient desks to the toilet and shower. After all assets are built, an experiment is conducted using survey methods to measure the realistic level of assets. From these experiments obtained a realistic level of the assets made have an average value above 3.7 from a scale of 5, which means that the 3D assets made are approaching objects with photo-realism characteristics.